Impact of antibiotics on public health (World Journal of Experimental Biosciences, 2023)
One of the most important factors affecting public health is the use of antibiotics to treat infectious diseases. It is the most important medical discovery of the twentieth century, as antibiotics contributed to controlling many bacterial epidemics in addition to treating infectious diseases. The overuse of antibiotics, especially in developing countries, has a negative impact on public health. Therefore, many organizations have worked to establish strict policies for the use of antibiotics. The current study highlights the main types of antibiotics their mechanism of action against bacteria and their role in public health. Those who understood the One Health approach contributed to developing a policy and action plan to reduce the misuse of antibiotics as well as control bacterial resistance to these antibiotics. International organizations and research centers developed important policies and initiatives to limit the increase in bacterial resistance to antibiotics. The most important strategies used to confront antibiotic-resistant bacteria are to find alternative treatments, as well as developing health education fields, and provide warning curricula that highlight the danger of the decreased efficiency of antibiotics in treating diseases and epidemics. The ambitions for the future are great in this field, especially by supporting scientific research that relies on the use of alternatives to antibiotics in treating infectious diseases, in addition to setting clear policies that restrict unnecessary uses of antibiotics. It can be concluded from this study that the optimal and scientific use of antibiotics reflects positively on public health by reducing the outbreak of infectious diseases and that focusing on alternative antibacterial medicine will create hope for a better future against infectious diseases.